On the identity of Bithoracochaeta sociabilis Blanchard (Diptera: Muscidae): a new synonym of Atherigona orientalis Schiner - Patitucci, Luciano Damián; Mulieri, Pablo Ricardo; Mariluis, Juan Carlos (Zootaxa, 2012)
Everard Eells Blanchard (1889-1971) was a distinguished figure of the Argentinean entomology. During his productive career, Blanchard described numerous species of Diptera, mostly on Tachinidae and Sarcophagidae, and published more than 150 articles (Cortés 1973). Blanchard worked for many years at the “División de Zoología Agrícola, Ministerio de Agricultura y Ganadería” (Agricultural Zoology Division, Ministry of Agriculture and Livestock) and later (as director) at the “Instituto de Patología Vegetal (Institute of Plant Pathology). After Blanchard’s decease, most specimens of his collection were sent to “Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”, Capital Federal, Buenos Aires (MACN), and some few specimens were retained at “Instituto Nacional de Tecnología Agropecuaria”, Castelar, Buenos Aires (INTA) (Dr. Axel O. Bachmann, pers. comm.).